Mitochondrial Genome analysis and genetic charaterization of endangered Humphead Wrasse, Cheilinus Undula Tus (Ruppell, 1835) from Sabah, Malaysia - Pressly Matthew (2019)
Mitochondrial (mt) Deoxyribonucleic acid (DNA) loci have been employed in various marine taxa, including reef fishes with the objective of resolving phylogeny, assigning parentage and delineating haplotypes. In this study, complete mtDNA genome was sequenced and the D-Loop locus was applied to estimate the population status of the Humphead Wrasse (HHW) Chetllnus undulatus. The Humphead Wrasse (HHW) is a long-lived reef-associated fish and the largest member of wrasses (family Labridae). However, it is endangered throughout its natural distributional range, primarily due to being a target in the Live Reef Fish for Food Trade. Specimens tissue were collected from three localities in Sabah, i.e. Kota Kinabalu, Sandakan and Semporna. The objectives of this study are 1) to sequence the mtDNA of the HHW, and 2) to identify population structure using D-LOOP of the HHW. The result of the sequencing data assemblies yielded six mitochondrial genomes and deposited into the National Center for Biotechnology Information (NCBI) with the accession number MH675879, MH675880, MH688049, MH688050, MH688051, MH688052. The result from AMOVA and overall Fst (-0.02914) showed that all three population absent from population structuring despite geographical distinct. The AMOVA showed a variation (100%) arise within the population instead among population. The neutrality test from Tajima' D (Kota Kinabalu: -1.825 and Sandakan: -1.009), and more sensitive Fu's Fs Statistic (Kota Kinabalu: -3.9844 and Sandakan-1.149), and mismatch distribution showed unimodal graph pattern suggested as C undulatus undergoes recent population expansion. Haplotype frequency analysis produce a total 25 haplotypes whereas unique 11 haplotype is detected from three local population. High haplotypic diversity encountered in the Kota Kinabalu (0.682), Sandakan (0.902) and Sempona (1.000) and low nucleotide diversity in Kota Kinabalu (0.003), Sandakan (0.004), and Semporna (0.002), and starburst pattern of common haplotypes median joining network support C undulatus population expansion. The first genetic characterization data from mtDNA and all three populations structure analysis of C undulatus from Sabah study provide a new insight for conservation attention.